Factors Influencing Undergraduate Students' Intention to Use Security and Privacy Protection Measures of Social Networking Sites: "A Case Study in Mogadishu University" - Mohamoud, Abdulkadir Jeilani (2021)
Social networking sites (SNSs) have simplified the way people communicate and interact with each other, in addition to the benefits of using social media, there are also privacy risks surrounding the posting of personal data details on social media. Furthermore, students are vulnerable to cyber security attacks because their account was created by his/her friend. This resulting, to a lot of weakness and poor risk management. Therefore, the primary goal of this research is to advance students’ intent while using social media through successful security and privacy-setting awareness. Four sub-objectives were investigated to reach the primary purpose of the study. The first sub objective was to investigate students’ awareness of security and privacy settings offered by social networking site providers. The second sub-goal of this study was to identify the impact of perceived training, value, attitude towards share, perceived benefit, and perceived severity attack on students’ intention to use security and privacy safety options in social media. The third sub-goal of this study was to identify the comprehensive approach to making the students use the security and privacy measures in Social Networking Sites (SNSs). The fourth sub-objective of this study was to propose a suitable model (framework) for promoting security and privacy protection measures in Social Networking Sites (SNSs). This research is based on already recognized models: the model Protection Motivation Theory (PMT), the Technology Acceptance Model (TAM), and the Theory of Reasoned Action (TRA). The researcher sought empirical suggestions for the validation of the theoretical model and hypotheses. A web-based survey instrument was developed that contains 45 –items survey using Likert-type scales. The target population of this study was undergraduate students at Mogadishu University (Freshman, sophomore, junior and senior). The sample for this study was 378 students with and high response rate. Descriptive analysis was used to accomplish the objectives of the study. The structural equation modeling technique was utilized to investigate both measurement model testing (reliability and validity) and structural models (hypotheses testing) to determine the factors influencing students’ intention to use security and privacy protection measures in social media by undergraduate students. A pilot study was conducted to get valuable feedback about the questionnaire, and the researcher tested the validity and reliability of the gathered data through the questionnaire. The Cronbach's alpha reliability score of each item (independent variables and dependent variable) exceeded the recommended value of 0.70. the range of level of internal reliability became between 0.939 and 0.818. this result illustrates that the measurement of the questionnaire items is reliable and can be used in the study. The results revealed that perceived training, severity attack, perceived value, perceived benefits, and attitude toward share have a positively related to students' intention to use security and privacy safety option in social networking sites (SNSs); perceived awareness was not significant to the student's intention to use security and privacy safety option.